2010
DOI: 10.1007/s12572-011-0026-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase-field based simulation of microstructure evolution in technical alloy grades

Abstract: Scope of the present article is to review the current state of the art with respect to simulation of microstructure evolution based on the multiphase-field approach in technical alloy grades. Starting from a short overview about computational thermodynamics and kinetics and respective databases for technical alloys, an engineering approach to phase-field and multiphase-field models will be depicted in order to allow for a basic explanation of these methods-in general being developed by physicists and mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 97 publications
(123 reference statements)
0
14
0
Order By: Relevance
“…This approach is implemented in the MICRostructue Evolution Simulation Software MICRESS® [13] and includes direct coupling to Calphad databases using efficient extrapolation algorithms [14,15] as well as other additional features which are detailed in [16,17]. This tool has been successfully used for simulations of phase transformations in a number of technical alloy systems [18][19][20][21]. The important and central role of applied microstructure simulations and their potential in ICME settings has already been demonstrated using this software tool [22].…”
Section: Phase-field Modelingmentioning
confidence: 99%
“…This approach is implemented in the MICRostructue Evolution Simulation Software MICRESS® [13] and includes direct coupling to Calphad databases using efficient extrapolation algorithms [14,15] as well as other additional features which are detailed in [16,17]. This tool has been successfully used for simulations of phase transformations in a number of technical alloy systems [18][19][20][21]. The important and central role of applied microstructure simulations and their potential in ICME settings has already been demonstrated using this software tool [22].…”
Section: Phase-field Modelingmentioning
confidence: 99%
“…Higher order derivatives of the order parameter eventually lead to atomic resolution of rigid lattices in so called phase-field crystal models [15]. Currently, phase-field models have reached a high degree of maturity and found applications in describing complex microstructures in technical alloy systems [16]. Reviews on phase-field modelling are found, for instance, in [17,18].…”
Section: Phase-field Modelsmentioning
confidence: 99%
“…dendrites during phase-transitions.They even entered into materials engineering and process design tasks [17]. Similar to the Heaviside function Θ the phase-field Φ is a field describing the presence respectively the absence of an object, fig.2.…”
Section: Phase-field Description Of a Geometric Objectmentioning
confidence: 99%